PENGGUNAAN GAYA MUSIK KLASIK DI DALAM IBADAH GEREJA KARISMATIK - Sasongko, Hari (Sekolah Tinggi Teologi Kristus Alfa Omega, 2017)
The church Â music has long history. It beganÂ when they, the believers, Â mentioned themselves as the â€œChristianâ€. The existence of church Â music more Â developed till middle age Â or Â dark Â age Â period. Â The church music Â was Â dominantly Â covering Â toÂ others Â music Â genre. Â At the Â Renaisance Â Period Â the Â church Â reformation movement occured and it was pioneeredÂ by Martin Luther. Western music changed at the time. Luther changed the tradition Â of CatholicÂ church that used Latin lirics to folk language. Â At the present day we are familiar with charismatic Â music traditionÂ which is developed from American music tradition. Â It has a charracteristic which is used as the band instrument in praiseÂ and worship by christian Â believers. But sometimes, the believers also use arpeggio Â or broken-chord Â as the main character on Classical Â Period Â in part the way of Western music history. Pass through the reasearch, the reasearcher look into the idioms are used in praise and worship in STT Kristus Alfa Omega Â Semarang. Â The researcher found that Â the usingÂ of idiom in Classical Â Period Â have enriched Â the nuance of music aesthetic in praise and worship